Micotoxinas no milho roxo peruano - Adaniya, Zoila Naeko Coloma (2017)
Purple corn is a variety of corn that is produced in the Peruvian Andes. Its characteristic color is by the presence of the pigment called antiocyanine that presents antioxidant, antimutagenic, anticancer and anti-diabetic properties. These characteristics have made that in addition to being used as a dye, is used as raw material in the elaboration of several by-products. Currently Peru exports this input, however, due to the lack of regulation and because it is considered an organic product, mycotoxin analyzes are not required. These toxins can be produced by filamentous fungi at any stage of the maize food chain. Its consumption by humans or animals can cause carcinogenic, mutagenic, hepatotoxic, estrogenic, immunotoxic and nephrotoxic effects, which is why international organisms have established maximum tolerable limits (MTL) of mycotoxins in foods to try to control exposure. Considering the possible effects of mycotoxins on consumers of Peruvian purple maize, the objective was to determine the presence of mycotoxins in this corn through LC-MS/MS. A total of 82 samples of purple maize were obtained from different Peruvian markets in two periods: December 2015 to March 2016 and March to April 2017. The mycotoxins analyzed were aflatoxins, fumonisins, zearelenone, ochratoxin A and the following trichothecenes: deoxynivalenol, nivalenol, fusarenone X, deacetoxyscirpenol, 3-acetyl-DON, HT-2 and T-2. It was verified that the most prevalent mycotoxins were aflatoxins and fumonisins, with a prevalence of 64.6 and 63.4%, respectively, with co-occurrence of these two mycotoxins in 45.1% of the samples. Only one sample had a quantifiable concentration for zearalenone and any sample was contaminated by ochratoxin A and trichothecenes. Considering the MTLs implemented by the European Community (EC, 2006, 2007, 2013), 12% of the analyzed samples had concentrations higher than the MTL of 1000 μg kg-1 for fumonisins and one sample had MTL of 10 μg kg-1 higher for aflatoxins. However, considering the Brazilian legislation, 9.8% of the samples had levels above the MTL of 5000 μg kg-1 of fumonisins (BRASIL, 2011, 2013, 2017). This is the first research that evaluates the occurrence of mycotoxins analyzed by LC-MS/MS in Peruvian purple maize and identifies that maize may constitute a source of intoxication, posing a risk to public health. Controls are required in the production chain of this grain and the implementation of legislation with MTLs of mycotoxins.